2021
DOI: 10.3847/1538-4357/ac1c03
|View full text |Cite
|
Sign up to set email alerts
|

3-OGC: Catalog of Gravitational Waves from Compact-binary Mergers

Abstract: We present the third open gravitational-wave catalog (3-OGC) of compact-binary coalescences, based on the analysis of the public LIGO and Virgo data from 2015 through 2019 (O1, O2, O3a). Our updated catalog includes a population of 57 observations, including 4 binary black hole mergers that had not been previously reported. This consists of 55 binary black hole mergers and the 2 binary neutron star mergers, GW170817 and GW190425. We find no additional significant binary neutron star or neutron star–black hole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
88
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 102 publications
6
88
1
Order By: Relevance
“…These include, amongst others, a BNS merger that was observed in the entire electromagnetic window from gamma-rays to radio waves (GW170817) [9,12,13], systems in which black hole (BH) companions have masses that could not have resulted from the evolution of massive stars (thus raising questions as to their origin, GW170729 [14] and GW190521 [15,16]), binaries that show a clear signature of sub-dominant octupole radiation in addition to the dominant quadrupole (confirming once again predictions of general relativity, GW190412 [17] and GW190814 [18]), and a binary with a mass-ratio of almost 1:10 that challenges astrophysical BBH formation models while its secondary companion could well be the heaviest neutron star (NS) or the lightest BH observed so far (GW190814 [18]). GW catalogs compiled by other groups [19][20][21][22][23] have largely confirmed the population of coalescing compact bina-These discoveries have already made a massive impact on our understanding of different tenets of astrophysics, fundamental physics, and cosmology. They have allowed a first glimpse into the dynamics of strongly curved spacetimes and the validity of general relativity (GR) in unexplored regimes of the theory [29][30][31][32][33][34], raised deeper questions on the formation mechanisms and evolutionary scenarios of compact objects [16,18,[35][36][37][38][39][40][41][42][43][44][45][46], provided a new tool for measuring cosmic distances that will help in precision cosmology [47,48]<...>…”
Section: Introductionmentioning
confidence: 93%
“…These include, amongst others, a BNS merger that was observed in the entire electromagnetic window from gamma-rays to radio waves (GW170817) [9,12,13], systems in which black hole (BH) companions have masses that could not have resulted from the evolution of massive stars (thus raising questions as to their origin, GW170729 [14] and GW190521 [15,16]), binaries that show a clear signature of sub-dominant octupole radiation in addition to the dominant quadrupole (confirming once again predictions of general relativity, GW190412 [17] and GW190814 [18]), and a binary with a mass-ratio of almost 1:10 that challenges astrophysical BBH formation models while its secondary companion could well be the heaviest neutron star (NS) or the lightest BH observed so far (GW190814 [18]). GW catalogs compiled by other groups [19][20][21][22][23] have largely confirmed the population of coalescing compact bina-These discoveries have already made a massive impact on our understanding of different tenets of astrophysics, fundamental physics, and cosmology. They have allowed a first glimpse into the dynamics of strongly curved spacetimes and the validity of general relativity (GR) in unexplored regimes of the theory [29][30][31][32][33][34], raised deeper questions on the formation mechanisms and evolutionary scenarios of compact objects [16,18,[35][36][37][38][39][40][41][42][43][44][45][46], provided a new tool for measuring cosmic distances that will help in precision cosmology [47,48]<...>…”
Section: Introductionmentioning
confidence: 93%
“…Since the first detection of gravitational waves (GW) from the merger of two compact objects in 2015 (Abbott et al 2016), GW science has come a long way and GW detections have become a routine (Abbott et al 2021a;Nitz et al 2021b). LIGO observatories in Livingston and Hanford (Aasi et al 2015) have already finished three science runs, namely O1, O2, and O3 (Abbott et al 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…The GW observatories: Virgo (Acernese et al 2015) in Italy and KAGRA in Japan (Akutsu et al 2021) joined the LIGO-Hanford and LIGO-Livingston observatories in O2 and O3 respectively. Currently, there are more than 90 confident GW detections from the merger of compact objects as identified by various data analysis pipelines summed up as GWTC-3 catalog (Abbott et al 2021a) and 4-OGC catalog (Nitz et al 2021b). In the upcoming decade, the network of ground base GW detectors is set to be expanded with the addition of LIGO-India (Saleem et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Refs. Wang et al (2021a,c) reported a new upper limit 4.5 × 10 −16 m by using the third open gravitational-wave catalog Nitz et al (2021), which includes the events during the first half of the third observing run (O3a). Model-dependent studies on the CPT symmetry can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%